Analisis Pengaruh Budaya Organisasi Dan Kepemimpinan Terhadap Kinerja Karyawan (Studi Pada Karyawan PT. Radar Ambon) - Tamalene, Abdul Haris; Rumadaul, Masila (P3M Politeknik Negeri Ambon, 2024)
As a company that publishes Print Media, PT Radar Ambon is faced with increasingly sharp competition, namely with the emergence of various online media, this has become a threat to the company. Thus, hard work is needed to improve employee performance through improving organizational culture and employee discipline, such as office hours, customer service and carrying out work in accordance with company norms and rules, so that it is hoped that employee performance will increase. With a good organizational work culture and high leadership, employees will have the enthusiasm to complete their tasks and responsibilities so that company performance can improve. Based on the multiple linear regression test, it shows that organizational culture variables influence employee performance. PT. Ambon Radar. This is because the calculated t value is greater in the t table value (tcount 3.059 > ttable 1.721) and the significance value is smaller than 0.05 (sig value 0.006 < Probability 0.05). And based on multiple linear regression testing in this research, it is known that leadership influences employee performance. The calculated t value is equal to the leadership variable which is 3.058. > ttable 1.721 with a significance value of 0.006 < 0.05 so there is a significant influence. Keywords: Culture, Discipline and Performance